Women on the edge? representations of the post-war suburban woman in popular culture to the present day (2013)
As the chapters up until now have demonstrated, ‘suburbia’ is not only a topological construction but also connotes a set of attitudes, mores and values. It is ‘safe’ space. In the popular imagination, it exists as gendered space: where a code of good housekeeping prevails as women tend to the nest (i.e. household and children), while their men are out in the big bad city earning a living. Suburbs were seen as a space of ‘ideal home . . . for women and children fi rst’ (Pile et al. 2000 :31). Clapson ( 2003 :125) notes the feminine suburbs have tended to be pitted against the macho-thrusting city for they ‘signify domesticity, repose, closeness to nature, lack of seriousness, mindlessness, and safety’. Chambers ( 2001 :78) has spoken of how the advertising campaigns for home electrics in the leisure and domestic spheres represented a utopian American suburbia in which the family was sacrosanct.’ Th e stereotypical suburban daily routine established in 1950s-set suburban television shows sees besuited males kiss goodbye to their wives and kids en route to the daily commute to offi ce leaving her to cheerfully perform household chores, for example baking sometimes with a housemaid/ cook. Th e weekend consists of car washing and barbecues.